Analisis Pengembangan SDM, Pelatihan Kerja, dan Motivasi terhadap Produktivitas Karyawan PT NASCO (INDOPINE) di Deli Serdang - Anisa Simanungkalit; Juniarti Juniarti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study was conducted to determine the effect of human resource development analysis, job training and motivation on employee productivity at PT Nasco (Indopine) in Deli Serdang Regency. The approach method used is a quantitative approach with a type of quantitative descriptive research in the form of numbers and statistical analysis using SPSS Version 26. The population of this study were all employees of PT Nasco (Indopine) in Deli Serdang Regency totaling 68 employees, while the sampling technique was Non Probability Sampling using Saturated Sampling because the entire population was sampled if the population was below 100. The results of this study indicate that human resource development has a positive and significant effect partially on employee work productivity with a tcount > ttable value (15.492 > 1.99714), job training has a positive and significant effect partially on employee work productivity with a tcount > ttable value (3.122 > 1. 99714) and motivation has a positive and significant effect partially on employee work productivity with a tcount > ttable (5.689> 1.99714) and simultaneously human resource development, job training and motivation have a positive and significant effect on employee work productivity at PT Nasco (Indopine) in Deli Serdang Regency with a value of fcount > ftabel (865.735 > 2.75). The results of this study indicate that partially and simultaneously H1 is accepted and H0 is rejected. While the resulting coefficient of determination is 97.5% and the remaining 2.5% is explained by other independent variables not examined in this study.